Facile Synthesis of [Cu(SCH3)]∞ Nanowires with High Charge Mobility. Issue 4 (4th February 2014) - Zhang, Yuliang; Xia, Ting; Yu, Kin Man; Zhang, Fuhua; Yang, Heng; Liu, Boyang; An, Yan; Yin, Yansheng; Chen, Xiaobo
Abstract [Cu(SCH3)]∞ nanowires with lengths on the order of hundreds of micrometers were obtained with a facile method from the reaction of Cu(NO3)2⋅3 H2O, dimethyl sulfoxide (DMSO), and water under hydrothermal conditions within a large range of DMSO/water ratios and at various temperatures. These highly crystalline, thermally stable (under vacuum) nanowires are p‐type conducting and have a hole mobility as high as 2 cm2 V−1 S−1, which is 102–105 times higher than previously reported values. The high hole mobility may demonstrate their promising future in various electronic‐device applications.